SISTEM PENDUKUNG KEPUTUSAN DALAM MENENTUKAN GARDENER TERBAIK MENGGUNAKAN ALGORITMA PROFILE MATCHING - Latif, Muhammad Abdul; Sembiring, Rahmat W.; Suhada, Drs. (STMIK Budi Darma, 2019)
PT.ISS Indonesia is the best and the largest Integrated Facility Service company in Indonesia with service coverage for Facility services, catering services, access control and parking.There are several fields in the company, one of which is the gardener. Gardener is one of the important parts in the company that is responsible for plant maintenance and gardening of a government agency or lodging company. A gardener has responsibility in terms of providing flowers for decoration in rooms such as rooms, lobbies, restaurants and rest rooms. The selection of the best gardener is done manually so that it requires a strong memory and accuracy for a leader.To overcome this, a system is needed to support the mindset of a leader in making objective decisions. There are several methods in decision support systems that can be used, one of which is the Profile Matching algorithm, which is a simple method in decision support systems by comparing GAP between alternative values and criteria.It is hoped that this research can provide a solution in recommending the best gardener in the company.So that it can facilitate the leadership in making decisions.Keywords : decision support systems, best gardener,Â profile matching